Robles in Lagunas de Epulauquen, Argentina: previous and recent evidence of their distinctive character - Azpilicueta, Maria Marta (2014)
The northernmost ‘robles’ of Argentina, located in Lagunas de Epulauquen (northwest Patagonia), are considered a population of Nothofagus obliqua, even though they differ in some respects from individuals of other populations of the species. In order to analyse a possible genetic basis of their distinctive character, we revised previous information and added new evidence based on biochemical (isozyme) and molecular (chloroplast DNA and nuclear microsatellite) markers, as well as quantitative trait variation (seed traits, leaf morphology, plant architecture and field performance). The comparison of Lagunas de Epulauquen specimens with specimens from other areas in Argentina demonstrated their genetic distinction. Glacial history, in conjunction with hybridisation processes, provides support for the main hypothesis to explain these results. Future research lines are proposed, aimed at identifying the taxonomic status of the Lagunas de Epulauquen population. The conservation value of these forests is highlighted.